Solid Biofuels from Hydrothermal Carbonization: A Comparative Study on Woody and Non-woody Biomass Material - Saidatul Shima, Jamari; Jonathan, H. R.; Sharifah Fathiyah, Sy Mohamad; Tanveer, K. A. (AENSI Publishing, 2014)
The transition of energy route from fossil fuels to renewable fuels, offer an opportunity to waste material, specifically biomass, in the energy production business. Biomass is a well-known waste material that has heterogeneous nature. This complicated nature poses a barrier on the competitiveness of biomass in the energy generation market. One of the methods is through the hydrothermal carbonization process. It is also proven through various experiments that the hydrothermal carbonization process has the ability to convert different type of biomass into higher carbon products. However, the complexity of biomass in nature shows that various chemical and physical characteristics were reported. Therefore, in this study, a comparison between carbon products from woody and non-woody agricultural waste via hydrothermal carbonization was done. Wood chips (WC) were chosen for the woody type of biomass, while for the non-woody, the oil palm empty fruit bunch (EFB) was chosen. The hydrothermal carbonization process occurs in the excess water with the addition of citric acid as the catalyst. The reaction process occurs in a pressure vessel for temperature, 220°C at different operating time. The chemical (elemental analysis, proximate analysis, fourier transform infrared spectroscopy (FTIR), thermagravimetric analysis (TGA),) and physical characteristic (field emission scanning electron microscopy (FESEM) andgas pyconometer) ratio) of the carbon products were verified. The hydrothermal carbonization process converts the EFB and WC into higher percentage of carbon content solid products. The carbon conversion of EFB‟s carbon increased for 20% compared to the raw EFB (43.8% of carbon). Based on the FESEM pictures, the formation of globular structure on the EFB biocarbons‟ surface area can be seen, while, severe damages on the fibres can be observed on the morphology of WC biocarbons. In general, carbon products from hydrothermal carbonization process have the ability to produce more energy compared to their raw materials. However, the non-woody biomass product has higher carbon conversion and combustion ability compared to the woody biomass‟ carbon.